Ta’lim al-Sharfi li al-Muta’allim al-Mubtadi’ ala Asasi Iktisab al-Lughah - Najah, Muhajirun (Asalibuna, 2019)
Learning in a simple way is an effort to influence someone’s emotional, intellectual and spiritual to want to learn at their own volition. There are many elements that can influence some of these things and become the obligation of educators as facilitators in learning to prepare and apply them. Language learning is very closely related to applied linguistics that discusses how a language can be obtained. one of the material materials in learning Arabic which is closely related to linguistics is shorof. The research aims to find out how shorof learning with language acquisition models. This study uses descriptive qualitative methods, and the conclusions obtained in this study are in the form of various kinds of shorof learning difficulties experienced by teachers and students, and the development of shorof learning with language acquisition models so that the teaching of learning is no longer a material that is difficult for students to master.